Peran Psikologi Manajemen dalam Proses Pemecahan Masalah Organisasi - Tiara Rahmadona; Suci Ramadhani; Sulastia, Sulastia; Merika Setiawati (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to examine the role of management psychology in the organizational problem-solving process. Organizational problems arise not only from structural and technical aspects but are also influenced by psychological factors of individuals and groups, such as perception, motivation, emotions, and work interaction dynamics. This study employs a literature review method by analyzing scientific journals and reference books related to management psychology and organizational behavior. The findings indicate that management psychology plays an important role in supporting comprehensive problem identification, improving decision-making quality, and enhancing the effectiveness of problem-solving through effective communication, teamwork, and cognitive bias management. The application of management psychology enables organizations to develop more accurate, adaptive, and sustainable solutions in addressing organizational challenges.